2018
DOI: 10.1111/jfd.12810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pseudomonas H6 surfactant on all external life cycle stages of the fish parasitic ciliate Ichthyophthirius multifiliis

Abstract: A bacterial biosurfactant isolated from Pseudomonas (strain H6) has previously been shown to have a lethal effect on the oomycete Saprolegnia diclina infecting fish eggs. The present work demonstrates that the same biosurfactant has a strong in vitro antiparasitic effect on the fish pathogenic ciliate Ichthyophthirius multifiliis.Three life cycle stages (the infective theront stage, the tomont and the tomocyst containing tomites) were all susceptible to the surfactant. Theronts were the most sensitive showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…As oregano essential oil has been shown to be effective in prevention of infection with Ichthyobodo and Trichodina in Oncorhynchus keta (Mizuno et al, 2018), we also tested oregano and found it to be effective in killing amoebae at a concentration of 17.9 mg/ml and partly effective at a concentration of 8.9 mg/ml. The bacterial lipopeptide surfactant H6 was previously shown effective against theronts of the ciliate Ichthyophthirius (Al‐Jubury et al, 2018), and it was lethal to Vannella sp. but in a 25 times higher concentration (250 µg/ml).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As oregano essential oil has been shown to be effective in prevention of infection with Ichthyobodo and Trichodina in Oncorhynchus keta (Mizuno et al, 2018), we also tested oregano and found it to be effective in killing amoebae at a concentration of 17.9 mg/ml and partly effective at a concentration of 8.9 mg/ml. The bacterial lipopeptide surfactant H6 was previously shown effective against theronts of the ciliate Ichthyophthirius (Al‐Jubury et al, 2018), and it was lethal to Vannella sp. but in a 25 times higher concentration (250 µg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…from tilapia ( Oreochromis niloticus ) (Chitmanat, Tongdonmuan, & Nunsong, 2005), from European eel ( Anguilla anguilla ) (Madsen, Buchmann, & Mellergaard, 2000), Ichthyophthirius multifiliis from rainbow trout ( O. mykiss ) (Buchmann, Jensen, & Kruse, 2003) and Ichthyobodo and Trichodina from Oncorhynchus keta (Mizuno et al, 2018). In addition, a bacterial lipopeptide, a biosurfactant isolated from Pseudomonas (strain H6), is able to kill the oomycete Saprolegnia diclina infecting fish eggs (Liu et al, 2015) as well as three life cycle stages of the pathogenic ciliate Ichthyophthirius multifiliis (Al‐Jubury et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A biosurfactant isolated from a Pseudomonas strain had strong in vitro antiparasitic effect against the fish pathogenic ciliate Ichthyophthirius multifiliis . Further, effective doses (10 to 100 ug/mL) exhibited no adverse effects in rainbow trout fingerlings exposed to the biosurfactant, indicated the antiparasitic potential of the biosurfactant [ 82 ]. Phospholipopeptide BS isolated from Staphylococcus hominis was assessed for immunostimulatory activity in Oreochromis mossambicus [ 83 ].…”
Section: Application Of Microbial Surfactants In Boosting the Immumentioning
confidence: 99%
“…The infected fish may mount a protective immune response (Bauer, 1953; Burkart, Clark, & Dickerson, 1990; Buschkiel, 1910; Dickerson & Clark, 1998; Goven, Dawe, & Gratzek, 1980; Hines & Spira, 1974; Moreira, Shoemaker, Zhang, & Xu, 2016; Sigh & Buchmann, 2001; Wang, Yu, Zhang, & Xu, 2019), but the experimental vaccines investigated so far (Burkart et al., 1990; He et al., 1997; Jørgensen et al, 2017; Ling, Sin, & Lam, 1993; Martins, Xu, Shoemaker, & Klesius, 2011; Wang, Clark, Noe, & Dickerson, 2002; Xu, Zhang, Shoemaker, & Beck, 2019) have not yet resulted in a marketable protective formulation. A number of chemotherapeutants have been successfully applied in the laboratory (Al‐Jubury et al., 2018; Picon‐Camacho, Marcos‐Lopez, & Shinn, 2012), but at farm level frequent usage of formalin, peracetic acid, sodium percarbonate and hydrogen peroxide remains the preferred control strategy (Heinecke & Buchmann, 2009; Meinelt et al., 2009; Rach, Gaikowski, & Ramsay, 2000). A genetic component associated with susceptibility and resistance to infection has been suggested in rainbowfish (Gleeson, McCalum, & Owens, 2000), leaving relevant possibilities for genetic selection of disease‐resistant strains.…”
Section: Introductionmentioning
confidence: 99%